Epigenetic consequences of nucleosome dynamics. - Ahmad, K.; Henikoff, S. (Cell, 2002)
Current models for epigenetic gene silencing envision a static relationship between histone modifications and transcription. However, evidence for nucleosome mobility and replacement favors a dynamic model that may explain phenomena ranging from variegation to the neural restriction of Rett syndrome.